PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - MOHAMMAD BUKHORI; ERLYANA KUSUMA DEWI (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2018)
Thisresearch istoknowthe influence ofwork discipline, physicalwork environmenttoemployee performance throughwork motivationasintervening variable ofproductionpartofPT.PertaminaEP Asset 5Field Sangasangaineast Kalimantan. Thisresearch wasconducted by surveymethodon77employeesofPT. PertaminaEPAsset5FieldSangasangainEastKalimantan.The result of analysis and discussion shows that: (1) work disciplinehasnegativeeffectonemployee'sperformance,(2) physicalwork environmenthaspositiveeffectonemployee'sperformance,(3) workdisciplinehas positiveeffectonworkmotivation,(4)thephysicalworkenvironmenthasapositive effectonworkmotivation,(5) work disciplinehasanegativeeffect onemployee performance, (6) work discipline has negative effect on employee performance throughworkmotivationasinterveningvariable,(7) physicalworkenvironment positively influenceto employeeperformance throughwork motivationasintervening variable.